St John’s Wort (Hypericum perforatum L.) in Broiler Nutrition - Özgün Işık; Helin Atan; Figen Kırkpınar; Ayşe Betül Avcı (Turkish Journal of Agriculture: Food Science and Technology)
Nowadays, the concept of sustainability is important in poultry meat production as in every field. The health status of the birds must be well-stated for sustainable broiler production. Considering that synthetics attract reactions and some of them are banned or limited, the use of natural feed additives for health protection has been the focus of research attention. St John’s wort is a plant that can positively affect the health of animals with bioactive components such as the hypericin it contains. St John’s wort or hypericum (Hypericum perforatum L.) has antiviral and antimicrobial effects in broilers and positively affects on blood biochemical parameters. This positive effect on health level also improves performance. The review aims to give information about St John’s wort and to examine a limited number of studies on their use in the diet of broilers.